High mean corpuscular volume as a predictor of esophageal cancer: A cohort study based on the Japanese Shizuoka Kokuho Database - Shinsuke Sato; Emi Ohata; Eiji Nakatani; Philip Hawke; Hatoko Sasaki; Erina Nagai; Yusuke Taki; Masato Nishida; Masaya Watanabe; Ko Ohata; Hideyuki Kanemoto; Akira Sugawara (PLoS ONE, 2025)
Mean corpuscular volume (MCV) is known to increase with alcohol and tobacco consumption, and is therefore a potential predictive marker for esophageal cancer onset. However, this potential has not previously been examined using a large database. This study aims to clarify whether MCV is a predictor of esophageal cancer onset using health checkup data from a comprehensive health insurance claims database of a major administrative district in Japan. Health checkup data for 582,342 individuals recorded between April 2012 and September 2020 in the Shizuoka Kokuho Database were analyzed. Risk factors were assessed using both univariable and multivariable Cox proportional hazards models. Within the cohort, 1,562 health checkup participants (0.27%) had been diagnosed with esophageal cancer during the study period. Multivariable analysis revealed that risk of esophageal cancer onset was predicted by hypertension, smoking, systolic blood pressure, alcohol consumption, alcohol use disorder, body mass index, low-density lipoprotein cholesterol, and MCV. The cutoff value of MCV for predicting esophageal cancer onset was 104.086 fl. These results suggest that it may be appropriate to carry out endoscopy to detect esophageal cancer when MCV, a well-known indicator of alcohol and tobacco consumption, is greater than 104 fl.